Audit on postnatal venous thromboembolism risk assessment. (18th April 2012) - Sathish, C; Mehta, G; Mohammed, S; Chakravarti, S
Abstract : Thromboembolism has been the leading cause of direct maternal deaths until the previous triennia. It has now dropped to be the III leading cause of direct maternal deaths, the drop being statistically significant (CMACE). The current VTE(venous thrombo embolism) risk assessment tool devised by RCOG is now in place in most hospitals. Aim: To audit whether VTE risk assessment tool is being adhered to during the postnatal period. Standards: RCOG guideline and hospital guideline for VTE risk assessment. Materials & Methods: Retrospective audit. 100 sets of notes were looked into randomly in the postnatal ward over 4week period, irrespective of mode of delivery. Conclusions: 78% had risk assessment done of which 73% were assessed right. 3% had wrong dose and 8% had wrong duration of Clexane. Risk assessment was missed in 1 (out of 4) morbidly obese patients and 3 out of 28 Emergency LSCS patients (independent risk factors for intermediate risk). Recommendations: To increase awareness among health professionals to use the VTE risk assessment tool on delivery suite before transfer to postnatal ward and improved layout of the assessment tool in order to achieve 100% target.